2014
DOI: 10.1111/jch.12340
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐Induced Pulse Wave Velocity Changes in Untreated Patients With Essential Hypertension: The Effect of an Angiotensin Receptor Antagonist

Abstract: 2This study investigates arterial stiffness changes after acute exercise in young patients with untreated, recently diagnosed grade I essential hypertension (UH) compared with normotensive (NT) individuals and the effect of antihypertensive treatment on this phenomenon. Study 1 consisted of 25 UH and 15 NT patients. UH patients who received treatment were included in study 2 and were followed-up after a 3-month treatment period with an angiotensin II receptor blocker. Aortic pulse wave velocity (PWV) was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 32 publications
7
29
1
Order By: Relevance
“…The reliability coefficient, or smallest detectable change, in the immediate response of PWV after exercise (1Á9 m s À1 ) was similar to the change in PWV previously observed after exercise (increase of~2Á0 m s À1 ) in adults with untreated grade I hypertension (Gkaliagkousi et al, 2014). Given the excellent reliability of the PWV response to exercise in older adults, the utility of this measurement as a prognostic marker should be considered.…”
Section: Reliability Of Arterial Stiffness Indices During Exercise Resupporting
confidence: 72%
See 1 more Smart Citation
“…The reliability coefficient, or smallest detectable change, in the immediate response of PWV after exercise (1Á9 m s À1 ) was similar to the change in PWV previously observed after exercise (increase of~2Á0 m s À1 ) in adults with untreated grade I hypertension (Gkaliagkousi et al, 2014). Given the excellent reliability of the PWV response to exercise in older adults, the utility of this measurement as a prognostic marker should be considered.…”
Section: Reliability Of Arterial Stiffness Indices During Exercise Resupporting
confidence: 72%
“…We also observed a transient decrease in AIx75 and reflection magnitude to below resting levels after exercise. Elevations in arterial stiffness following exercise in obese and hypertensive adults (Shim et al, 2011;Gkaliagkousi et al, 2014;Moon et al, 2015;Bunsawat et al, 2017) are potentially detrimental and may be due to underlying dysfunction of these mechanisms. While resting measures of arterial stiffness reflect structural and functional mechanisms, beneficial reductions in arterial stiffness during recovery following acute exercise in healthy adults are suggested to be functional and are likely mediated by reductions in central blood pressure (Millen et al, 2016), vasoconstrictors (endothelin-1) (Schreuder et al, 2014) and sympathetic nerve activity (Heffernan et al, 2007), alongside increases in nitric oxide bioavailability and endothelial function (Campbell et al, 2011).…”
Section: Variablementioning
confidence: 99%
“…Of importance, despite the post‐exercise reduction in systolic BP levels, the increase in cf‐PWV persisted, even after 30 minutes of recovery in hypertensive patients. As expected, systolic BP and cf‐PWV levels at all 5 timepoints of the baseline exercise test were significantly higher in hypertensive patients than in controls …”
supporting
confidence: 81%
“…Until recently, the only available data in hypertensive patients on the effects of acute high‐intensity exercise on aortic stiffness were derived from a small study (9 treated hypertensive individuals) which showed that acute dynamic exercise did not influence distensibility or β stiffness index of carotid and brachial arteries . The study by Gkaliagkousi and coworkers advances our knowledge in the field of acute cardiovascular effects of high‐intensity exercise, showing that the treadmill aerobic test was associated with a transient deterioration of elastic properties of the aorta in young patients with untreated, newly diagnosed essential hypertension, whereas this harmful effect was not evident in age‐ and sex‐matched healthy individuals. This study further expands previous findings which show that treatment with the ARB valsartan for 3 months can ameliorate this exercise‐induced increase in aortic stiffness.…”
mentioning
confidence: 99%
“…Laurent and colleagues report on higher central systolic BP and aortic stiffness in aerobically trained individuals, which is in contrast to several other studies that have shown beneficial effect. Moreover, there also seem to be racial differences regarding the response of arterial compliance to exercise as well as differences in hypertensive and normotensive patients …”
mentioning
confidence: 99%